Regulaciones de calidad en la competitividad de exportadoras de camarón de El Oro al mercado europeo - Cordova Alarcon, Grace Monserrate (Machala : Universidad Técnica de Machala, 2025)
This essay analyzes the impact of quality regulations on the competitiveness of shrimp exporting companies from El Oro province to the European market. It highlights the relevance of the shrimp sector as Ecuador’s main non-oil export and its significant share of national trade. The research, conducted with a mixed and descriptive non-experimental approach, employed documentary, bibliographic, and interview techniques with executives of exporting companies. The findings reveal that compliance with international standards and certifications is a decisive factor for entry and permanence in demanding markets such as the European Union. In addition, opportunities for improvement in production practices, quality management, and sustainability were identified, which strengthen the competitiveness of the sector and contribute to the national economy.
El presente ensayo analiza la incidencia de las regulaciones de calidad en la competitividad de las empresas exportadoras de camarón de la provincia de El Oro hacia el mercado europeo. Se destaca la relevancia del sector camaronero como principal rubro no petrolero del Ecuador y su participación en las exportaciones nacionales. La investigación, con enfoque mixto, descriptivo y de tipo no experimental, emplea técnicas documentales, bibliográficas y entrevistas a directivos de empresas exportadoras. Los resultados evidencian que el cumplimiento de normas y certificaciones internacionales constituye un factor determinante para la inserción y permanencia en mercados exigentes como la Unión Europea. Asimismo, se identifican oportunidades de mejora en las prácticas productivas, la gestión de la calidad y la sostenibilidad, lo que permite fortalecer la competitividad del sector y aportar a la economía nacional.
Keywords: REGULACIONES DE CALIDAD; COMPETITIVIDAD; EXPORTACIONES DE CAMARÓN; UNIÓN EUROPEA